Effect of structural stability on endolysosomal degradation and T‐cell reactivity of major shrimp allergen tropomyosin. Issue 11 (18th June 2020) - Kamath, Sandip D.; Scheiblhofer, Sandra; Johnson, Christopher M.; Machado, Yoan; McLean, Thomas; Taki, Aya C.; Ramsland, Paul A.; Iyer, Swati; Joubert, Isabella; Hofer, Heidi; Wallner, Michael; Thalhamer, Josef; et al.
Abstract: Background: Tropomyosins are highly conserved proteins, an attribute that forms the molecular basis for their IgE antibody cross‐reactivity. Despite sequence similarities, their allergenicity varies greatly between ingested and inhaled invertebrate sources. In this study, we investigated the relationship between the structural stability of different tropomyosins, their endolysosomal degradation patterns, and T‐cell reactivity. Methods: We investigated the differences between four tropomyosins—the major shrimp allergen Pen m 1 and the minor allergens Der p 10 (dust mite), Bla g 7 (cockroach), and Ani s 3 (fish parasite)—in terms of IgE binding, structural stability, endolysosomal degradation and subsequent peptide generation, and T‐cell cross‐reactivity in a BALB/c murine model. Results: Tropomyosins displayed different melting temperatures, which did not correlate with amino acid sequence similarities. Endolysosomal degradation experiments demonstrated differential proteolytic digestion, as a function of thermal stability, generating different peptide repertoires. Pen m 1 (Tm 42°C) and Der p 10 (Tm 44°C) elicited similar patterns of endolysosomal degradation, but not Bla g 7 (Tm 63°C) or Ani s 3 (Tm 33°C). Pen m 1–specific T‐cell clones, with specificity for regions highly conserved in all four tropomyosins, proliferated weakly to Der p 10, but did not proliferate to Bla g 7 and Ani s 3, indicating lack of T‐cell epitope cross‐reactivity. Conclusions: Tropomyosin T‐cell cross‐reactivity, unlike IgE cross‐reactivity, is dependent on structural stability rather than amino acid sequence similarity. These findings contribute to our understanding of cross‐sensitization among different invertebrates and design of suitable T‐cell peptide‐based immunotherapies for shrimp and related allergies. Abstract : Allergenic tropomyosins have dissimilar structural stabilities despite having high amino acid sequence similarity. Tropomyosins are differentially degraded in the endolysosomal compartment of antigen‐presenting cells due to differences in their structural stability. Tropomyosin T‐cell cross‐reactivity, unlike IgE antibody cross‐reactivity, is dependent on structural stability rather than amino acid sequence similarity.